Tracheostomy trends in preterm infants with bronchopulmonary dysplasia in the United States: 2008–2017. Issue 5 (1st February 2021) - Donda, Keyur; Agyemang, Christfelly O.; Adjetey, Naa A.; Agyekum, Afua; Princewill, Nimitariye; Ayensu, Marian; Bray, Leonita; Yagnik, Priyank J.; Bhatt, Parth; Dapaah‐Siakwan, Fredrick
Abstract: Objective: To determine the trends in tracheostomy placement and resource use in preterm infants less than or equal to 30 weeks gestational age (GA) with bronchopulmonary dysplasia (BPD) in the United States from 2008 to 2017. Study design: This was a retrospective, serial cross‐sectional study using data from the NIS. Inclusion criteria were: GA less than or equal to 30 weeks, hospitalization at less than or equal to 28 days of age, assignment of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD9‐CM) or ICD10‐CM codes for BPD and tracheostomy. Trends in tracheostomy and resource utilization were assessed using Jonckheere–Terpstra test. p ‐value < .05 was considered significant. Results: Overall, 987 out of 68, 953 (1.4%) hospitalizations with BPD had tracheostomy. Characteristics of the study population: 60.8% were male, 68.4% less than or equal to 26 weeks GA, 43.8% White, 60.5% with Medicaid or self‐pay, 65.2% in the Midwest and South census regions of the United States, and 45.7% had gastrostomy tube placement. Tracheostomy placement (expressed as per 100, 000 live births) decreased from 2.7 in 2008 to 1.9 in 2011. Thereafter, it increased from 1.9 in 2011 to 3.5 in 2017 ( p < .001). GA less than or equal to 24 weeks was significantly associated with increased odds of tracheostomy placement. Median length of stay increased significantly from 170 to 231 days while median inflation adjusted hospital cost increased significantly from 323, 091 in 2008–2009 to 687, 141 between 2008–2009 and 2016–2017. Conclusion: Although tracheostomy placement among preterm hospitalizations with BPD was rare, the frequency of its placement and its associated resource utilization significantly increased during the study period. Future studies should probe the reasons and factors behind these trends.